Plants wilt disease of red leaf lettuce (Lactuca sativa L.) after colonized by Trichoderma longibrachiatum - Mohd Sazali, Muhammad Iqbal Nul Hakim; Ab Aziz, Zakry Fitri; Kundat, Franklin Ragai (The Malaysian Society of Applied Biology, 2023)
Trichoderma longibrachiatum rarely reported can cause disease in plants. The present study investigates the pathogenicity of T. longibrachiatum isolate UPMT14 on the red leaf lettuce (Lactuca sativa L.) plants grown in sterile soil under a controlled growth room environment. The fungal isolate was initially characterized morphologically as Trichoderma sp. and was then further characterized by (ITS) region sequencing and BLAST comparison identified as T. longibrachiatum. To observe the response of Trichoderma isolate UPMT14 when imposed on lettuce plants. The injection was made and repeated five times, and then the lettuce growth followed for 36 days. On day 36, the present study found that the red leaf lettuce plants expressed foliar symptoms that began as chlorotic, reduced plant height, reduced leaf length and diameter, wilt, and dried up before it collapsed at day 45 compared to untreated control lettuce plants. Microscopic observation on lettuce roots showed that the Trichoderma spores invading the root system by mass sporulation and spatial competition possibly impaired plant water uptake and eventually caused plant wilting. Therefore, this study indicates that T. longibrachiatum is among the causal agents of wilt disease in the lettuce plant.